STRATEGI KEPALA SEKOLAH DALAM PEMBENTUKAN KEDISIPLINAN PENDIDIK DAN PESERTA DIDIK DI MTs AT-TAUFIQ BOGEM DIWEK JOMBANG - Abidah, Tasbihul; Aminuddin Aziz, Abdullah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Discipline is important in the teaching and learning process at school, the person who plays an important role in discipline at school is the principal, as someone who is very influential in the formation of discipline, the principal must have a strategy in realizing discipline at school. This research uses qualitative research methods. From the results of the study it can be concluded (1) the principal's strategy at MTs At-Taufiq Bogem Diwek Jombang is to be able to be multitalented and must be ready in any situation, must be fair and able to think creatively, (2) the discipline of educators and students at MTs At-Taufiq Bogem Diwek Jombang has three main points, among others: compiling discipline, delivering discipline and giving punishment, (3) the principal's strategy in shaping the discipline of educators and students is to play a good role model, always remind and repeat to obey order, Inviting educators to monitor student behavior. Providing additional activities that are carried out every day, aims to instill a disciplined attitude in every school citizen in general and students in particular, (4) the impact of the principal's success in shaping the discipline of educators and students is very good, such as being accustomed to performing worship diligently, also has an impact on academics such as more enthusiasm for learning, not noisy during lessons, educators are able to condition the class. Impact on morals such as mutual respect, mutual respect. The impact on the school itself, the atmosphere of the school environment becomes calm and makes the community more confident and willing to send their children to this school.